2013
DOI: 10.1134/s0006297913110096
|View full text |Cite
|
Sign up to set email alerts
|

Construction and functional analysis of novel dominant-negative mutant of human SOX18 protein

Abstract: SOX18 transcription factor plays important roles in a range of biological processes such as vasculogenesis, hair follicle development, lymphangiogenesis, atherosclerosis, and angiogenesis. In this paper we present the generation of a novel SOX18 dominant-negative mutant (SOX18DN) encoding truncated SOX18 protein that lacks a trans-activation domain. We show that both wild-type SOX18 (SOX18wt) and truncated human SOX18 proteins are able to bind to their consensus sequence in vitro. Functional analysis confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…It has been observed that SOX18 takes part in wound healing processes and the development of atherosclerosis (19). Likewise, an increased level of this protein has been found in melanomas and malignant pancreatic, stomach and breast tumors (21).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that SOX18 takes part in wound healing processes and the development of atherosclerosis (19). Likewise, an increased level of this protein has been found in melanomas and malignant pancreatic, stomach and breast tumors (21).…”
Section: Introductionmentioning
confidence: 99%
“…The predicted truncated protein generated by the p.Gln181stop variant identified in this individual would disrupt the central TAD and also result in loss of the C‐terminal TAD. Functional studies of a truncated SOX18 protein that lacks the C‐terminal TAD retains its DNA binding capacity while having a dominant‐negative effect on its other protein binding properties (Milivojevic et al, ). We speculate the truncated protein predicted by the proband's nonsense variant would likely exert a similar dominant‐negative effect on SOX18 transcriptional activities, ultimately resulting in his phenotypic features.…”
Section: Discussionmentioning
confidence: 99%
“…SiHa (ATCC, HTB-35) and Ca Ski (ATCC, CRL-1550) were maintained in Dulbecco's Modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS). Transfection experiments were carried out as previously described[ 23 , 24 ]. For co-transfection experiments, 10 μg of promoter reporter construct (892pCAT6) was co-transfected with 2 μg of either pcDNA4NLSMTGLI1, p4TO6MTGLI2 or pcDNA4/TO/GLI3 expression constructs[ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…For imunocytochemistryanalysis, cells were cultured in 24 well dishes and GLI1, GLI2 or GLI3 were co-transfected with pEGFP-C1 (Clontech Laboratories, Mountain View, CA, USA) in ratio 9:1 using Lipofectamine (Invitrogene, NY, USA). For functional analysis of SOX18 protein, cells were transfected as previously described[ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation